HUBUNGAN ANTARA PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN BAHASA ANAK USIA 12-36 BULAN DI PUSKESMAS TAMAMAUNG MAKASSAR - Soamole, Rahayu; Asnaniar, Wa Ode Sri; Taqiyah, Yusrah; Sharief, Suchi Avnalurini (Universitas Islam Negeri Alauddin Makassar, 2018)
Exclusive breastfeeding is breastfeeding a pure baby, where the baby is only given breast milk for 6 months without additional fluids or other foods. The benefits of breastfeeding have been documented worldwide, but only 39% of children under 6 months get exclusive breastfeeding. The purpose of this study was to determine the relationship between exclusive breastfeeding and language development of children aged 12-36 months in the Work Area of Makassar Tamamaung Health Center. The research design used was an analytic survey with a cross sectional study approach. This study uses purposive sampling with a sample size of 40 respondents. Relationship test was conducted using Chi-Square statistical test with a significance level of α = <0.05.The results showed that there was a relationship between exclusive breastfeeding and children's language development in the work area of the Tamamaung Makassar Public Health Center (ρ = 0.021).Based on the results of the study, it showed that there was a relationship between exclusive breastfeeding and the development of children's language in the Tamamaung Makassar Health Center Work Area. For this reason, it is suggested to the relevant parties to provide intensive counseling to mothers, especially to young mothers who have children about the importance of exclusive breastfeeding for child growth and development.